2006
DOI: 10.1038/sj.onc.1209997
|View full text |Cite
|
Sign up to set email alerts
|

Snail silencing effectively suppresses tumour growth and invasiveness

Abstract: The transcription factor Snail has been recently proposed as an important mediator of tumour invasion because of its role in downregulation of E-cadherin and induction of epithelial-mesenchymal transitions (EMT). This behaviour has led to the consideration of Snail as a potential therapeutic target to block tumour progression. In this report, we provide evidence for this hypothesis. We show that silencing of Snail by stable RNA interference in MDCK-Snail cells induces a complete mesenchymal to epithelial trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
204
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(229 citation statements)
references
References 36 publications
21
204
3
1
Order By: Relevance
“…Importantly, the effect of shSnai2 is specific as it did not influence Snai1-EGFP mediated repression of E-cadherin promoter (Supplementary Figure S1B). As previously reported, shSnai1 is specific for Snail1 repression (Supplementary Figure S1B; Olmeda et al, 2007a).…”
Section: Shsnai2 Inhibits Snai2 Expression Without Affecting Snai1mentioning
confidence: 56%
See 3 more Smart Citations
“…Importantly, the effect of shSnai2 is specific as it did not influence Snai1-EGFP mediated repression of E-cadherin promoter (Supplementary Figure S1B). As previously reported, shSnai1 is specific for Snail1 repression (Supplementary Figure S1B; Olmeda et al, 2007a).…”
Section: Shsnai2 Inhibits Snai2 Expression Without Affecting Snai1mentioning
confidence: 56%
“…Previous studies on human breast carcinoma cells also suggested a differential involvement of Snai1 and Snai2 in E-cadherin repression or specific invasion patterns (Hajra et al, 2002;Come et al, 2006). We recently described an important role for Snai1 in tumor growth, differentiation and invasion of mouse skin (Olmeda et al, 2007a), and in lymph node metastasis of human breast carcinoma cells (Olmeda et al, 2007b). Now, we have investigated the interplay between Snai1 and Snai2 in tumorigenesis targeting each factor by stable RNA interference in two mouse skin carcinoma cell lines, analysing their effect in in vitro invasion, and tumorigenic and metastatic behaviour into nude mice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Snail 1 has recently been shown to revoke the inhibition of the Wnt/beta-Catenin pathway caused by the anti-tumoral compound 1α,25-dihydroxyvitamin D3 [16,17]. Snail 1 is upregulated and frequently associated with invasiveness, metastases and poor prognosis in several human cancers [18][19][20][21][22]. Snail 1 is upregulated (in tumor-stroma interphase) in 60-70 % of colorectal adenoma and colorectal cancers [23].…”
Section: Introductionmentioning
confidence: 99%